An-nisa’iyah as an Epistemological Framework in Islamic Education: Advancing Gender Justice, Spiritual Agency, and Educational Reform - Jakiyem, Jakiyem; Bakar, M. Yunus Abu; Mas'ud, Ali; Abdurakhmonovich, Yuldashev Azim (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This article examines an-nisa’iyah as a critical epistemological paradigm within Islamic education, offering a framework that advances gender justice, spiritual empowerment, and women’s autonomy. Rooted in a response to persistent patriarchal narratives in some Islamic educational settings, an-nisa’iyah rearticulates the role of women as active moral, intellectual, and social agents. Utilizing literature review and critical discourse analysis, this study investigates how an-nisa’iyah can inform educational reform across curriculum, pedagogy, and praxis—particularly in both formal and non-formal learning environments. The concept encourages an Islamic pedagogy that fosters awareness of rights, capabilities, and ethical responsibilities among female learners. By situating spirituality as integral to liberation, an-nisa’iyah envisions education as a space for nurturing independent, critically conscious Muslim women. The article argues that integrating this paradigm within Islamic educational systems may contribute to more inclusive, justice-oriented, and spiritually grounded learning models—thus reshaping Islamic education into a transformative vehicle for gender equity and social renewal.